Strategi Resiliensi Museum dan Galeri Foto Jurnalistik Antara Menghadapi Pandemi Covid-19 - Nurul Aldha Mauliddina Siregar; Ute Lies Siti Khadijah; Evi Novianti (Institut Seni Indonesia Yogyakarta, 2021)
The implementation of the Large-Scale Social Restrictions (PSBB) policy in order to reduce the number of transmission of the coronavirus (Covid-19) pandemic cases in Jakarta leads several cultural heritage sites such as museums close the physical access to visits. In the midst of these limitations, the Antara Journalistic Museum and Photo Gallery made a breakthrough by establishing the museum digitization approach using Video Reality (VR) technology. This article was written to see how the strategy for the resilience of Cultural Heritage Sites in the Museum and Journalistic Photo Gallery is between maintaining some journalistic photo exhibition agendas amidst the lack of public interest in visiting museums plus the threat of a multidimensional crisis due to the Covid-19 pandemic. This research was written using qualitative methods with a descriptive approach. The existence of this facility provides a new alternative for the public to continue visiting and accessing journalistic photo exhibition programs and activities which have been regularly held at the Antara Museum and Photo Journalistic Gallery so far. Having concern with the strength of the mission to preserve historical value as one of the broadcasting spaces for independence and to disseminate journalistic knowledge, especially related to the photojournalism to the younger generation and the strong encouragement of the community, the Antara Journalistic Photo Gallery and Museum is encouraged to survive and continue to operate in organizing activities that have been consistently scheduled yearly.